2014
DOI: 10.1111/exd.12584
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of BRAF,NRAS and c‐KIT mutation status between tumor tissues and autologous tumor cell‐lines of stage III/IV melanoma

Abstract: In the last decade, advances in molecular biology have provided evidence of the genotypic heterogeneity of melanoma. We analysed BRAF, NRAS and c-KIT alterations in tissue samples from 63 stage III/IV melanoma patients and autologous cell-lines, using either allele-specific or quantitative PCR. The expression of BRAF V600E protein was also investigated using an anti-BRAF antibody in the same tissue samples. 81% of FFPE samples and tumor cell-lines harboured a genetic alteration in either BRAF (54%) or NRAS (27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…It was assumed that patients with Stage III melanoma would not undergo BRAF testing in the absence of adjuvant therapy with dabrafenib and trametinib. Accordingly, patients receiving dabrafenib and trametinib were assigned the cost of BRAF testing, accounting for the costs of patients who would test negative [21][22][23][24][25][26][27][28][29][30][31][32][33] , and the costs of retesting for patients with invalid initial test results 34 . Patients receiving observation who experience disease recurrence were assumed to undergo BRAF testing to inform metastatic treatment.…”
Section: Costsmentioning
confidence: 99%
“…It was assumed that patients with Stage III melanoma would not undergo BRAF testing in the absence of adjuvant therapy with dabrafenib and trametinib. Accordingly, patients receiving dabrafenib and trametinib were assigned the cost of BRAF testing, accounting for the costs of patients who would test negative [21][22][23][24][25][26][27][28][29][30][31][32][33] , and the costs of retesting for patients with invalid initial test results 34 . Patients receiving observation who experience disease recurrence were assumed to undergo BRAF testing to inform metastatic treatment.…”
Section: Costsmentioning
confidence: 99%
“…6 Estimates of the percentage of melanoma patients with BRAF mutation were based on a meta-analysis of studies identified by a targeted review of the literature. [7][8][9][10][11][12][13][14][15][16][17][18][19] Estimates of the proportion of Stage III cases that are successfully resected (90%) were based on clinical expert opinion and data from SEER. 20 It was conservatively assumed that all eligible patients would be treatment naive.…”
Section: Eligible Populationmentioning
confidence: 99%
“…A successful TKI, Imatinib, demonstrates its anti-angiogenic activity against multiple targets, including v-Abl, c-Kit, and PDGFR ( Knol et al, 2015 ). Recent reports showed that c-Kit mutations were more common in acral and mucosal melanomas ( Knol et al, 2015 ; Sabbah et al, 2021 ). In a study, 130 KIT-altered melanoma patients were pooled from five medical centers ( Jung et al, 2022 ).…”
Section: Anti-angiogenic Agents In Melanomamentioning
confidence: 99%